Correct use of the “Bishop’s process” in adjudicating nullity of marriage - Rozkrut, Tomasz (Prawo Kanoniczne, 2021)
A few years have passed since Pope Francis amended the method of adjudicating nullity of marriage by the Church courts in 2015. The time that passed, especially the experience gained during the time, encourages one to raise a question on the correctness of usage of the amendment introduced in the process law that is, unarguably, bold. In particular, the question should relate to the “abbreviated process” that, due to its specificity, can also be called the “Bishop’s process”. An important moment to take up the topic of the correct usage of the abbreviated process before a bishop is an article published by G. P. Montini that pertains to unlawful use of processus brevior (G.P. Montini, L’uso illegittimo del processus brevior. Rimedi processuali ordinari e straordinari, Periodica 108 (2019) 35-72). The Pope Francis’ reform has clearly determined that the requisite of evident nullity of marriage is essential not only at the beginning of the process, but it must be present in the course of the entire evidentiary proceedings that is to result in a positive judgement, so that an accusation that the processus brevior is conducted illegally cannot be made. Selected elements picked out from the court practice suggest that things that are the most essential for the analysed method of adjudication of the marriage nullity by the authority of the Church must be reminded in a synthetic manner. Therefore, the following problematic aspects have been singled out: selected assumptions of the Pope Francis’ process reform of 2015, process tasks and obligations of a diocesan bishop, selected practical remarks relating to the “Bishop’s process”. A correct use of the “Bishop’s process” in adjudicating nullity of marriage should not only contribute to solving specific issues of conscience, which without any doubts constitutes its important purpose, but can also be used to present the Church as a proficient institution. Thereby, it can contribute to raising the Church’s prestige and authority in the present world. Undoubtedly, the signalled abnormalities that appeared in particular interpretations that are discordant with the Pope Francis process reform’s spirit and the letter of the reform must be seen from this perspective. It is important that the errors are skilfully corrected and fixed. This is the more important that this is the Church proceedings, the central figure of which is bishop. An important issue, to which the Pope Francis’ practical pontiff draws attention is, unarguably, personal responsibility for decisions made in the Church, which specifically relates to the authorities of the Church. For people in the Church also make errors, for which they bear responsibility and should face their consequences. Their precise specification and successive remediation will make the Church a trustworthy institution in the present world. Furthermore, this will allow it to shape consciences of the faithful and fulfil the received mission in an appropriate manner.